2019
DOI: 10.1186/s12936-019-2975-8
|View full text |Cite
|
Sign up to set email alerts
|

Human exposure to Anopheles farauti bites in the Solomon Islands is not associated with IgG antibody response to the gSG6 salivary protein of Anopheles gambiae

Abstract: Background Mosquito saliva elicits immune responses in humans following mosquito blood feeding. Detection of human antibodies recognizing the Anopheles gambiae salivary gland protein 6 (gSG6) or the gSG6-P1 peptide in residents of Africa, South America and Southeast Asia suggested the potential for these antibodies to serve as a universal marker to estimate human biting rates. Validating the utility of this approach requires concurrent comparisons of anopheline biting rates with antibodies to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 22 publications
5
21
0
Order By: Relevance
“…In the same way, Pollard et al suggested that the antibodies to the gSG6-P1 peptide in the Colombian population may represent exposure to An. punctimacula, which is a member of the Anopheles subgenus or could hypothetically represent exposure to minor vectors in the country [31]. Thus, the current results suggest that the gSG6-P1 peptide could be a useful marker for malaria risk in areas of Colombia where mosquitoes belonging to subgenus other than Nyssorhynchus are present.…”
Section: Discussionmentioning
confidence: 68%
“…In the same way, Pollard et al suggested that the antibodies to the gSG6-P1 peptide in the Colombian population may represent exposure to An. punctimacula, which is a member of the Anopheles subgenus or could hypothetically represent exposure to minor vectors in the country [31]. Thus, the current results suggest that the gSG6-P1 peptide could be a useful marker for malaria risk in areas of Colombia where mosquitoes belonging to subgenus other than Nyssorhynchus are present.…”
Section: Discussionmentioning
confidence: 68%
“…Antibody responses against the Anopheles gambiae salivary gland protein gSG6 or the synthetic peptide gSG6-P1 have been correlated with mosquito exposure [ 94 , 102 ]. While these serological markers have been successfully validated at multiple sites in Africa, Asia, and Southeast Asia, other studies suggest that anti-gSG6 targets of local anopheline vectors are more reliable for estimating transmission intensity [ 103 106 ].…”
Section: Low Endemicity: Pre- and Post-malaria Eliminationmentioning
confidence: 99%
“…IgG responses to the Anopheles gambiae gSG6 or the gSG6-P1 peptide have been widely validated as marker of human exposure to Afrotropical malaria vectors in different epidemiological settings in Western and Eastern African countries (Poinsignon et al, 2008 ; Drame et al, 2010 ; Rizzo et al, 2011b ; Badu et al, 2012 ; Stone et al, 2012 ; Proietti et al, 2013 ; Yman et al, 2016 ). Moreover, the same antigens have been successfully employed for Asian malaria vectors (Ya-Umphan et al, 2017 ) and may be of some use with Polynesian (Idris et al, 2017 ; Pollard et al, 2019 ) and American Old World anophelines (Montiel et al, 2020 ). For Aedes mosquitoes some promising indications have been obtained with the Nterm-34kDa peptide, which is designed on the culicine-specific Ae.…”
Section: Introductionmentioning
confidence: 99%